Great waterworks in Roman Greece : aqueducts and monumental fountain structures : function in context - Aristodemou, Georgia A.; Tasios, Th. P., 1930- (Archaeopress Roman archaeology, 2018)
A presentation of large scale waterworks in the Greek provinces of the Roman Empire. As a collective work, it brings together a wide body of experts from the newly emerged and expanding field of water technology and water archaeology in Roman Greece, and it fills an essential gap in archaeological research.